SARS-CoV-2 genomic characterization and evolution in China - Peng Zhang; Dongzi Liu; Lei Ji; Fenfen Dong (Heliyon, 2023)
The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) affected global health worldwide due to its high contagiousness. During the viral spread, many mutations occurred within the virus genome. China has adopted nonpharmaceutical intervention (NPI) to contain COVID-19 outbreaks. In order to understand the evolution and genomic variation of SARS-CoV-2 in China under this policy, a total of 524 sequences downloaded from Global Initiative on Sharing All Influenza Data (GISAID) between 2019 and 2022 were included in this study. The time-scaled evolutionary analysis showed that these sequences clustered in three groups (Group A-C). Group B and C accounted for the majority of the sequences whose divergence times were around 2020 and distributed in multiple regions. Group A was mainly composed of G variants, which were mainly isolated from several regions. Moreover, we found that 191 sites had mutations with no less than 3 times, including 30 amino acids that were deleted. Finally, we found that spike and nucleocapsid genes underwent positive selection evolution, indicating that the mutations within spike and nucleocapsid genes increased the SARS-CoV-2 contagiousness. Hence, this study preliminarily elucidates the evolutionary characteristics and genomic mutations of SARS-CoV-2 under the implementation of the NPI policy in China, providing scientific basis for further understanding the control effect of the NPI policy on the epidemic.